Narratives Crossing Boundaries Storytelling in a Transmedial and Transdisciplinary Context - Friedmann, Joachim (Bild und Bit. Studien zur digitalen Medienkultur, 2023)
As the dominant narrative forms in the age of media convergence, films and games call for a transmedial perspective in narratology. Games allow a participatory reception of the story, bringing the transgression of the ontological boundary between the narrated world and the world of the recipient into focus. These diverse transgressions - medial and ontological - are the subject of this transdisciplinary compendium, which covers the subject in an interdisciplinary way from various perspectives: game studies and media studies, but also sociology and psychology, to take into account the great influence of storytelling on social discourses and human behavior.